Haloferax volcanii, a Prokaryotic Species that Does Not Use the Shine Dalgarno Mechanism for Translation Initiation at 5′-UTRs - Kramer, Piet (Public Library of Science, 2014)
It was long assumed that translation initiation in prokaryotes generally occurs via the so-called Shine Dalgarno (SD) mechanism. Recently, it became clear that translation initiation in prokaryotes is more heterogeneous. In the haloarchaeon Haloferax volcanii, the majority of transcripts is leaderless and most transcripts with a 5′-UTR lack a SD motif. Nevertheless, a bioinformatic analysis predicted that 20–30% of all genes are preceded by a SD motif in haloarchaea. To analyze the importance of the SD mechanism for translation initiation in haloarchaea experimentally the monocistronic sod gene was chosen, which contains a 5′-UTR with an extensive SD motif of seven nucleotides and a length of 19 nt, the average length of 5′UTRs in this organism. A translational fusion of part of the sod gene with the dhfr reporter gene was constructed. A mutant series was generated that matched the SD motif from zero to eight positions, respectively. Surprisingly, there was no correlation between the base pairing ability between transcripts and 16S rRNA and translational efficiency in vivo under several different growth conditions. Furthermore, complete replacement of the SD motif by three unrelated sequences did not reduce translational efficiency. The results indicate that H. volcanii does not make use of the SD mechanism for translation initiation in 5′-UTRs. A genome analysis revealed that while the number of SD motifs in 5′-UTRs is rare, their fraction within open reading frames is high. Possible biological functions for intragenic SD motifs are discussed, including re-initiation of translation at distal genes in operons.